Water Quality of the Kolar River Basin - Vairagade, D.M.; Juneja, H.D.; Jadhav, R.T.; Paliwal, L.I. (Asian Journal of Chemistry, 2010)
Electrical conductivity (EC) and sodium absorption ratio (SAR) values were determined for the surface water of Kolar river during post-monsoon and pre-monsoon periods. The analytical results show erratic EC and SAR values mainly due to tidal ingression. The point source effluent from the ash bund disposal waste water from Koradi Thermal Power Station of Maharashtra State Electricity Board (MSEB) shows higher values which decrease with river water dilution. However, when used for irrigation, it may affect the soil, crops, human life and cattle. The utility of Kolar river water for irrigation has been discussed. The river water contains low medium salinity. the calculated values of SAR, sodium per cent and magnesium hazard are in the ranges of 5.4 to 18.49,36.06 to 74.50 and 15.78 to 48.79.